Adoption of electronic supply chain management systems: the mediation role of information sharing - Pu, Xiaodie; Wang, Zhengxu; Chan, Felix T.S. (Emerald Group Holdings Ltd., 2020)
Purpose: Based on structural embeddedness theory and resource dependence theory, this research aims to examine the mediation role of information sharing in the relationship between deendency structures and electronic supply chain management system (eSCM) adoption and a firm's intention to adopt eSCMs. Design/methodology/approach: A survey questionnaire was undertaken from 212 companies based in Mainland China. Three-stage least squares (3SLS) regression was employed to test the research model. Findings: The results from 3SLS regressions showed that the effect of interdependence on eSCM adoption intention is fully mediated through information sharing when relationship duration is either below or about the mean. Interdependence and dependence disadvantage was shown to have significant positive effects on eSCM adoption while the effect of dependence advantage was statistically insignificant. Relationship duration was found to negatively moderate the relationship between information sharing and adoption intention. Originality/value: Through investigating factors of inter-organizational relationships, this study fills the knowledge gap in the traditional paradigms which ignore the collaborative nature of eSCM and analyse related problems based on a single firm's point of view.